Large scale distributed scientific data management and service technology framework and system - Feng LIU; Xin CHEN; Jianhui LI; Ang LIU; Fang HAN (大数据, 2016)
With the development of the information process,problems in the management and application of large-scale distributed With three decades of experience in related fields,after studying key issues and core requirements,the systematic toplevel design was conducted.The technical architecture for large-scale distributed scientific data in management and services was proposed,and the service system was organized and planned from three levels:autonomy management,integration management and integration services,also a complete service platform and software system were constructed to provide integration solutions for scientific data management and services from management to application.